Diskusi Penyusunan RPJMDES Dalam Mewujudkan Desa Tanggap Bencana (Studi Kasus Desa Paku) - Jamaluddin; Muhammad Muthahari Ramadhani; Muhammad Ridho Fauzi; Refina Damayanti Hutagalung; Ati; Muhammad Riswan Yustiwandi; Hayatun Nisa; Kurniawan Hidayat; Tri Utomo Putra (Wadah Inovasi Indonesia, 2021)
In development planning, a village must have a plan that can be used as a reference in implementing the development of a village, both in terms of physical and non-physical development. In accordance with Article 4 of Permendagri No. 114/2014, village development plans are prepared in a time-framed manner including: Village Medium-Term Development Plans (RPJM Desa) for a period of 6 years; and the Village Annual Development Plan or the so-called Village Government Work Plan (RKP Desa), is an elaboration of the Village RPJM for a period of 1 (one) year and is stipulated by village regulations. The method used in the preparation of the Paku Village Medium-Term Development Plan to realize a disaster-responsive village is the method of discussion or exchanging ideas between village officials. The initial stage of preparation in the preparation of the Village RPJM to be able to realize a disaster-responsive nail village. The discussion stage for the preparation of the RPJMDes of Paku Village was carried out at the Paku Village Head's Office and assisted by the Head of the RPJMDes Preparation Team, namely Mr. Kusnadiansyah and the Paku Village Head discussing the disaster response village.